A New Three-Dimensional Refined Higher-Order Theory for Free Vibration Analysis of Composite Circular Cylindrical Shells - Ali Davar; Reza Kohandani; Hamid Mohammad Panahiha (Mechanics of Advanced Composite Structures)
A new closed form formulation of three-dimensional (3-D) refined higher-order shell theory (RHOST) to analyze the free vibration of composite circular cylindrical shells has been presented in this article. The shell is considered to be laminated with orthotropic layers and simply supported boundary conditions. The proposed theory is used to investigate the effects of the in-plane and rotary inertias as well as transverse normal and shear strains on the dynamic response of thick composite cylindrical shells. The trapezoidal shape factor of the shell element is incorporated to obtain accurate stress-resultants. Using Hamilton’s principle, the equations of motion are obtained and solved in terms of the Galerkin method. Numerical results for the natural frequencies are verified by making comparison with the 3-D exact elasticity iterative solutions in the literature. In addition, the validity of the results is further verified by ABAQUS. According to the results, for thick composite cylinders with large length-to-radius and orthotropic ratios, through thickness exact integration yields accurate stress-resultants for proper prediction of the natural frequencies.